2006
DOI: 10.1128/jvi.80.8.3792-3800.2006
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Functional Domains in Herpes Simplex Virus 2 Glycoprotein B

Abstract: Glycoprotein B (gB) is one of four membrane proteins that are essential for the entry of herpes simplex viruses (HSV) into cells, and coexpression of the same combination of proteins in transfected cells results in cell fusion. The latter effect is reminiscent of the ability of virus infection to cause cell fusion, particularly since the degree of fusion is greatly increased by syncytial mutations in gB. Despite intensive efforts with the gB homologs of HSV and some other herpesviruses, information about funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 40 publications
2
26
0
Order By: Relevance
“…Previously it was shown that certain 2-aa insertions into HSV-1 gB or the closely related HSV-2 gB (85% identity) also permitted cell surface expression (15,16). These insertions map to the N-terminal region outside the solved structure (S48, A104: insertion sites in HSV-2 gB at positions equivalent to HSV-1 gB T53 and T109) and to the small N-terminal segment of domain III (P130), linker 1 (R136), domain I (R189, Y254, R304, T313, P358), domain II (G381, S403, G437), the disordered region between domain II and linker 2 (P483), domain V (D680), and the cytoplasmic tail (E816).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previously it was shown that certain 2-aa insertions into HSV-1 gB or the closely related HSV-2 gB (85% identity) also permitted cell surface expression (15,16). These insertions map to the N-terminal region outside the solved structure (S48, A104: insertion sites in HSV-2 gB at positions equivalent to HSV-1 gB T53 and T109) and to the small N-terminal segment of domain III (P130), linker 1 (R136), domain I (R189, Y254, R304, T313, P358), domain II (G381, S403, G437), the disordered region between domain II and linker 2 (P483), domain V (D680), and the cytoplasmic tail (E816).…”
Section: Resultsmentioning
confidence: 99%
“…Insertions after K70, K76, P80, and P81 had no effect on expression or function of gB, as assessed here. Similarly, insertions into HSV-2 gB at positions equivalent to HSV-1 gB T53 and T109 (S48 and A104 in HSV-2) had no effect on expression and only the insertion at A104 partially reduced function (16). Insertions K70 and K76 targeted a Lys-rich region from K68 to K76 shown to be critical for the binding of gB to heparin (20).…”
Section: Locations Of Insertions On Gb Structure In Relation To Effecmentioning
confidence: 99%
See 3 more Smart Citations